2012
DOI: 10.1007/s00420-012-0804-2
|View full text |Cite
|
Sign up to set email alerts
|

The influence of employment social support for risk and prognosis in nonspecific back pain: a systematic review and critical synthesis

Abstract: PurposeTo examine the influence of employment social support type (e.g. co-worker, supervisor, general support) on risk of occurrence of low back pain, and prognosis (e.g. recovery, return to work status) for those who have low back pain.MethodsSystematic search of seven databases (MEDLINE, Embase, PsychINFO, CINAHL, IBSS, AMED and BNI) for prospective or case–control studies reporting findings on employment social support in populations with nonspecific back pain. Data extraction and quality assessment were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 50 publications
(103 reference statements)
2
70
0
7
Order By: Relevance
“…The findings of a review study also revealed that perceived workload, time pressure and poor social support were the main psychological factors associated with MSDs prevalence (27). However, the findings of a systematic review by Campbell et al (2013) showed that there was no effect of co-worker, supervisor or general work support on risk of new onset back pain (28). There are limited knowledge regarding the association of work-related psychosocial factors and MSD in hospital nurses and most of the previous studies focused on physical demands like manual handling.…”
Section: 6mentioning
confidence: 98%
“…The findings of a review study also revealed that perceived workload, time pressure and poor social support were the main psychological factors associated with MSDs prevalence (27). However, the findings of a systematic review by Campbell et al (2013) showed that there was no effect of co-worker, supervisor or general work support on risk of new onset back pain (28). There are limited knowledge regarding the association of work-related psychosocial factors and MSD in hospital nurses and most of the previous studies focused on physical demands like manual handling.…”
Section: 6mentioning
confidence: 98%
“…It refers to the support people report having received or that is available to them if needed within the context of informal (e.g., family, friends) or formal relationships (e.g., healthcare services/professionals; Cohen et al 2000). Findings highlight the importance of social support in the experience of pain and pain-related outcomes such as disability (e.g., Campbell et al 2011;Campbell and Wynne-Jones 2013;Leonard et al 2006;Newton-John 2002). Most of this literature, however, has been focusing on the role of informal social support (from spouses or co-workers) on middle-aged adults' pain experiences.…”
Section: Introductionmentioning
confidence: 97%
“…As doenças da coluna lombar têm representado uma das principais causas de incapacidade e afastamento das atividades de trabalho por motivo de doença, representando cerca de 60% a 80% das doenças que atingem os trabalhadores (CAMPBELL et al, 2013). De acordo com Meziat Filho e Azevedo e Silva (2011), a dor nas costas é uma das principais causas de invalidez e de auxílio-doença no Brasil.…”
Section: Resultsunclassified